Testing the clinical value of multifocal electroretinography and microperimetry and the effects of intravitreal therapy with ranibizumab on macular function in the course of wet age-related macular degeneration: a 1-year prospective study - Reinsberg M (Dove Medical Press, 2017)
Mihaela Reinsberg,1 Ralf-Dieter Hilgers,2 Inger Lüdeke,1 Khaled Nassar,1 Swaantje Grisanti,1 Salvatore Grisanti,1 Julia Lüke,1,* Matthias Lüke1,* 1University Eye Hospital, University of Lübeck, Lübeck, 2Department of Medical Statistics, RWTH Aachen University, Aachen, Germany *These authors contributed equally to this work Purpose: To investigate the clinical value of multifocal electroretinography (mfERG) and microperimetry and the effects of intravitreal therapy with ranibizumab (Lucentis®) on macular function in the course of neovascular age-related macular degeneration (nAMD). Materials and methods: We conducted a prospective single-arm interventional cohort study with 20 nAMD patients older than 50 years. Examinations were scheduled monthly for 1 year during intravitreal therapy with ranibizumab. The examinations included mfERG, microperimetry, spectral domain optical coherence tomography, and best-corrected visual acuity using ETDRS score. Results: During the 12-month observation period, a significant positive linear correlation between the logarithm of minimum angle of resolution (logMAR) and scotoma area (r=0.28, 95% confidence interval [CI] 0.21–0.35), between logMAR and fovea thickness in optical coherence tomography (r=0.11, 95% CI 0.04–0.2), and a significant negative correlation between logMAR and mfERG (-0.37, 95% CI -0.43 to -0.31) were observed. A significant ranibizumab effect on logMAR was found (P=0.0065). From a total of 25 relapses, 14 were able to be predicted correctly by mfERG P1 decrease in the preceding month. However, there was no statistically significant relation between prediction and observed relapses (Fisher’s exact test, P=0.6726). Conclusion: Our results indicate a possible role of mfERG and microperimetry in the monitoring of macular function and prediction of recurrence during intravitreal pharmacotherapy in wet AMD. Keywords: macular function testing, microperimetry, multifocal electroretinogram, therapy monitoring